Pengaruh Emotional Quotient (EQ) terhadap Kemampuan Pemecahan Masalah - Siskawati, Fury Styo; MT, A Mujib; Rohman, Imdadur (LPPM Universitas Hasyim Asy'ari Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Abstract: This study aims to analyze the influence of Emotional Quotient (EQ) on students' mathematical problem-solving abilities on the topic of circles. EQ is considered a non-cognitive factor that plays an important role in managing emotions, stress, and learning motivation. This research method uses a quantitative approach with a simple linear regression analysis. Data were collected using an EQ questionnaire based on Goleman's five aspects and a problem-solving test based on Polya's steps. The results of the analysis show that EQ has a positive and significant effect on mathematical problem-solving abilities (p < 0.05). The coefficient of determination of 0.41 indicates that EQ contributes 41% to the variation in problem-solving abilities. This finding strengthens the theory that emotional intelligence is an integral part of academic success, especially in mathematics learning. Keywords: emotional quotient, problem solving